1991
DOI: 10.1128/mcb.11.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Determinants for glycophospholipid anchoring of the Saccharomyces cerevisiae GAS1 protein to the plasma membrane.

Abstract: A 125-kDa glycoprotein exposed on the surface of Saccharomyces cerevisiae cells belongs to a class of eucaryotic membrane proteins anchored to the lipid bilayer by covalent linkage to an inositol-containing glycophospholipid. We have cloned the gene (GAS)) encoding the 125-kDa protein (Gaslp) and found that the function of Gaslp is not essential for cell viability. The nucleotide sequence of GAS) predicts a 60-kDa polypeptide with a cleavable N-terminal signal sequence, potential sites for N-and 0-linked glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
197
1

Year Published

1996
1996
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(206 citation statements)
references
References 75 publications
(69 reference statements)
8
197
1
Order By: Relevance
“…The ω region is followed by a less defined spacer region of about 10 amino acids followed by a hydrophobic tail. The length of the C-terminal signal peptide normally varies between 15 and 30 residues (Udenfriend and Kodukula, 1995) but, as was shown in S. cerevisiae for Gas1, signal peptides of 31 residues do occur (Nuoffer et al, 1991). In the set of S. cerevisiae GPI proteins so obtained, Asn or Gly predominated at the GPI attachment site (Caro et al, 1997).…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…The ω region is followed by a less defined spacer region of about 10 amino acids followed by a hydrophobic tail. The length of the C-terminal signal peptide normally varies between 15 and 30 residues (Udenfriend and Kodukula, 1995) but, as was shown in S. cerevisiae for Gas1, signal peptides of 31 residues do occur (Nuoffer et al, 1991). In the set of S. cerevisiae GPI proteins so obtained, Asn or Gly predominated at the GPI attachment site (Caro et al, 1997).…”
Section: Introductionmentioning
confidence: 74%
“…The length and the hydrophobic character of the tail, rather than its specific sequence, therefore seem to be relevant for GPI anchoring (Ikezawa, 2002). Consistent with this, Coyne et al (1993) showed GPI modification of a truncated protein with a synthetic tail of at least 11 Leu residues, whereas introduction of a single charge in the middle of the hydrophobic tail blocks GPI anchoring (Nuoffer et al, 1991).…”
Section: Introductionmentioning
confidence: 91%
“…Interestingly, both Fks1p and Rho1p are also present in mitochondria (Sickmann et al, 2003). Gas1p, a putative ␤-1,3-glucan-remodeling enzyme (Popolo and Vai, 1999;Mouyna et al, 2000), the loss of which also results in reduced ␤-1,3-glucan in the cell wall (Popolo et al, 1993;Ram et al, 1998), is attached to the plasma membrane via a glycosyl-phosphatidylinositol anchor (Conzelmann et al, 1988;Nuoffer et al, 1991). Gas1p also is found in mitochondria (Grandier-Vazeille et al, 2001;Sickmann et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of immature ER forms of GPI proteins such as Gas1p (Nuoffer et al, 1991) or Cwp1p (Shimoi et al, 1995) is a symptom of a delay or deficiency in the GPI anchor addition to newly synthesized proteins (Doering and Schekman, 1996). Western blotting shows an accumulation of the immature 105-kDa form of Gas1p and the immature 45-kDa form of Cwp1p after 5 and 15 h of depletion of Gpi16p ( Figure 6A), whereas there was no accumulation of immature carboxypeptidase Y (CPY) (not shown).…”
Section: Gpi16p Is Essential For Gpi Anchoringmentioning
confidence: 99%